Altered Intermittent Rhythmic Delta and Theta Activity in the Electroencephalographies of High Functioning Adult Patients with Autism Spectrum Disorder - Endres, Dominique; Maier, Simon; Feige, Bernd; Posielski, Nicole A.; Nickel, Kathrin; Ebert, Dieter; Riedel, Andreas; Philipsen, Alexandra; Perlov, Evgeniy; Tebartz van Elst, Ludger (Frontiers in Human Neuroscience, 2017)
Background: Autism spectrum disorder (ASD) is often associated with epilepsy. Previous studies have also shown increased rates of electroencephalographic (EEG) alteration in ASD patients without epilepsy. The aim of this study was to compare the rate of intermittent rhythmic delta and theta activity (IRDA/IRTA) events between high-functioning adult patients with ASD and matched healthy controls. Materials and Methods: Routine EEG records of 19 ASD patients and 19 matched controls were screened for IRDA/IRTA using a fully data driven analysis with fixed thresholds. IRDA/IRTA rates before and after hyperventilation (HV) as well as the HV-induced difference in IRDA/IRTA rates (HV difference) were analyzed. For intra-group measures, we used the Wilcoxon signed rank test. Results: Significantly increased HV difference was detected in the ASD group (p=0.0497). However, the groups showed no difference in IRDA/IRTA rates before HV (p=0.564) and after HV (p=0.163). Conclusions: The lack of any group differences regarding IRDA/IRTA before HV might be related to the fact that we only studied non-secondary high-functioning autism in a small sample of epilepsy-free adult patients. A significantly increased HV difference might be regarded as a marker of subtle neuronal network instability possibly causing short-term disturbances via local area network inhibition and long-term effects via epileptic encephalopathy.